2001
DOI: 10.1017/s0952836901000413
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Zealand bats (Chalinolobus tuberculatus and Mystacina tuberculata) in flight from analysis of echolocation calls by artificial neural networks

Abstract: Time-expanded and heterodyned echolocation calls of the New Zealand long-tailed Chalinolobus tuberculatus and lesser short-tailed bat Mystacina tuberculata were recorded and digitally analysed. Temporal and spectral parameters were measured from time-expanded calls and power spectra generated for both timeexpanded and heterodyned calls. Arti®cial neural networks were trained to classify the calls of both species using temporal and spectral parameters and power spectra as input data. Networks were then tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 52 publications
0
47
1
1
Order By: Relevance
“…Other research into long-tailed bats in Kinleith Forest found they were detected more commonly along roads among P. radiata which were near harvest age, and that bat activity along a road in one area of P. radiata exceeded that along the same road where it passed through a nearby indigenous remnant (Moore 2001). Nevertheless, rates of detection of bats in Kinleith Forest were far lower than in comparable bat detector-based research in the native Nothofagus forest of Fiordland's Eglinton Valley (O'Donnell 2000a;Borkin & Parsons 2009), and whilst no direct relationship has yet been established between detection rates and actual numbers of bats present (Parsons 2001), we presume that this indicates a smaller population in Kinleith Forest.…”
Section: Long-tailed Bat Research In Plantation Forestcontrasting
confidence: 63%
“…Other research into long-tailed bats in Kinleith Forest found they were detected more commonly along roads among P. radiata which were near harvest age, and that bat activity along a road in one area of P. radiata exceeded that along the same road where it passed through a nearby indigenous remnant (Moore 2001). Nevertheless, rates of detection of bats in Kinleith Forest were far lower than in comparable bat detector-based research in the native Nothofagus forest of Fiordland's Eglinton Valley (O'Donnell 2000a;Borkin & Parsons 2009), and whilst no direct relationship has yet been established between detection rates and actual numbers of bats present (Parsons 2001), we presume that this indicates a smaller population in Kinleith Forest.…”
Section: Long-tailed Bat Research In Plantation Forestcontrasting
confidence: 63%
“…PARAMETRIC APPROACHES Parametric measurements taken e.g., from oscilloscopes, powerspectra or spectrograms allow for later analysis with a variety of approaches ranging from discriminant function analysis or DFA (Zingg 1990;Vaughan et al 1997;Jones et al 2000;Russo & Jones 2002) to decision trees (Herr et al 1997) and artificial neural networks or ANN (Stocker 1998;Parsons 2001). For measurements taken from data-reduced samples high recognition rates above 90% were reported for some species, others failed completely to be separated (Herr et al 1997).…”
Section: Data Reductionmentioning
confidence: 99%
“…One frequency dial on the Bat Box III detectors was set at c. 27 kHz (±4 kHz; Waters & Walsh 1994) corresponding with the peak amplitude of lesser short-tailed bat calls and the other on c. 40 kHz to correspond with peak amplitude of long-tailed bats (Parsons 2001). Total bat passes per hour per night were counted from the tapes.…”
Section: Indexing Bat Activitymentioning
confidence: 99%
“…Passes were generally classified as lesser short-tailed bats if they were recorded at 27 kHz and as longtailed bats if they were at 40 kHz. Although there is overlap between the fundamentals and harmonics of calls of both species (Parsons 1997), overlapping calls are distinguishable because lesser short-tailed bat call rates were twice as fast as those of longtailed bats (O'Donnell et al 1999;Parsons 2001). Verified reference tapes of both bat calls recorded in a variety of different habitat types were used as an additional aid to identification.…”
Section: Indexing Bat Activitymentioning
confidence: 99%
See 1 more Smart Citation